Comparison of Three RNA Extraction Methods for Gene Expression Analysis by RT-qPCR from Piperaceae Plants - ชูพยัคฆ์, ชนนิษฏ์; วรนุช, กำไร; บัวเรือง, รัตติกานต์; กงบังเกิด, อนุพันธ์ (KKU Science Journal, 2013)
Piperaceae plants are medicinal herbs that coexist with Thai society for a long time. Sesquiterpenes, the active components of those plants, have pharmacological interest. However, the complexity of molecular structure makes them still be expensive. Biotechnology should be the better choice for high quality and cheap chemical production. To achieve that goal, the regulation of biosynthetic gene expression needed to be studied that requires high quality of RNA. However, high phenolics and high chlorophyll contents in leaves obstructed RNA isolation from Piperaceae. The aim of this work was to obtain the efficient method for RNA isolation from P. betle, P. sarmentosum and P. retrofractum leaf. By comparison between different methods, RNeasy® Plant Mini kit (QIAGEN®), TRIzol® Reagent (Life technologies TM) and easy-REDTM RNA extraction (iNtRON Biotechnology), it was found that RNeasy® Plant was the most efficient method. RNA isolated from RNeasy® Plant method was high quality, integrity and equal amount from three tested plant species. Afterwards, RNeasy® Plant - isolated RNA was further used for gene expression analysis using RT-qPCR technique. It was demonstrated that the RNA could be used as a template for Actin and Sesquiterpene synthase transcript amplification. Taken together, RNeasy® Plant Mini kit was the ideal method for isolation of RNA from Piperaceae plants using for gene expression analysis and molecular study.